COVID-19-associated Coagulopathy Characterization using Rotational Thromboelastometry in a Prospective, Observational Cohort Study: The HemoCoV Study - Rodrigues, Anabela (2023)
Introduction: COVID-19-associated coagulopathy includes systemic and endothelial inflammation with coagulation dysregulation related to immunothrombosis. The aim of this study was to characterize this complication of SARS-CoV-2 infection in patients with moderate to severe COVID-19. Methods: An open-label, prospective observational study conducted in patients with COVID-19 moderate to severe acute respiratory failure admitted to an intensive care unit (ICU). Coagulation testing, including thromboelastometry, biochemical analysis and clinical variables, were collected at prespecified time points during the 30 days of ICU stay.Results: The study included 145 patients, 73.8% male, with a median age of 68 years (interquartile range - IQR 55 - 74). The most prevalent comorbidities were arterial hypertension (63.4%), obesity (44.1%) and diabetes (22.1%). Simplified acute physiology score II (SAPS II) was on average 43.5 (11 - 105) and sequential organ failure assessment (SOFA) at admission was 7.5 (0 - 14). During ICU stay, 66.9% of patients underwent invasive mechanical ventilation and 18.4% extracorporeal membrane oxygenation support; thrombotic and hemorrhagic events occurred in 22.1% and 15.1% of the patients respectively; anticoagulation with heparin was present in 99.2% of patients since early ICU stay. Death occurred in 35% of patients. Longitudinal studies revealed changes in almost all coagulation tests during the ICU stay. SOFA score, lymphocyte counts, some biochemical, inflammatory and coagulation parameters, including hypercoagulability and hypofibrinolysis seen in thromboelastometry, differed significantly (p < 0.05), between ICU admission and discharge. Hypercoagulability and hypofibrinolysis persisted throughout ICU hospitalization, showing higher incidence and severity in non-survivors.Conclusion: COVID-19-associated coagulopathy is characterized by hypercoagulability and hypofibrinolysis from ICU admission, and persisted throughout the clinical course in severe COVID-19. These changes were more pronounced in patients with higher disease burden and in non-survivors.